Analysis of Bub3 and Nup75 in the drosophila male germline lineage - Yildirim, Kerem; Nierop y Sanchez, Patrick van; Lohmann, Ingrid (Cells & development, 2023)
Extensive communication at the stem cell-niche interface and asymmetric stem cell division is key for the homeostasis of the Drosophila male germline stem cell system. To improve our understanding of these processes, we analysed the function of the mitotic checkpoint complex (MCC) component Bub3 and the nucleoporin Nup75, a component of the nuclear pore complex realizing the transport of signalling effector molecules to the nucleus, in the Drosophila testis. By lineage-specific interference, we found that the two genes control germline development and maintenance. Bub3 is continuously required in the germline, as its loss results in the beginning in an over-proliferation of early germ cells and later on in loss of the germline. The absence of the germline lineage in such testes has dramatic cell non-autonomous consequences, as cells co-expressing markers of hub and somatic cyst cell fates accumulate and populate in extreme cases the whole testis. Our analysis of Nups showed that some of them are critical for lineage maintenance, as their depletion results in the loss of the affected lineage. In contrast, Nup75 plays a role in controlling proliferation of early germ cells but not differentiating spermatogonia and seems to be involved in keeping hub cells quiescent. In sum, our analysis shows that Bub3 and Nup75 are required for male germline development and maintenance.
Online veröffentlicht am 5. Juni 2023
Gesehen am 13.12.2023